Development of a short‐form Health Literacy Dental Scale (HeLD‐14). Issue 2 (12th November 2014) - Jones, Kelly; Brennan, David; Parker, Eleanor; Jamieson, Lisa
Abstract Objective To develop a short‐form version of the 29‐item Health Literacy in Dentistry (HeLD‐29) instrument. Methods Deriving the short‐form version used data from a cross‐sectional study of 400 indigenous Australians aged 18+ years in Port Augusta, South Australia, which was split to enable short‐form testing (N = 191). Internal reliability analysis, factor analysis and regression analysis were undertaken to derive a subset (HeLD‐14) questionnaire. Its validity was evaluated by assessing associations with socio‐demographic and self‐reported oral health variables. Internal consistency of the HeLD‐14 was evaluated using Cronbach's coefficient α. A HeLD‐14 scale was derived from regression analysis. Results The HeLD‐14 accounted for 94% of variance in the HeLD‐29 mean scores; had high reliability (α = 0.88); contained questions from each of the seven conceptual dimensions of the HeLD‐29; and had a good distribution of prevalence for individual questions. HeLD‐14 scores and HeLD‐29 scores displayed the same pattern of variation among socio‐demographic groups of indigenous Australians. Cronbach's α for the HeLD‐14 was 0.87. In a multivariable analysis, the same socio‐demographic and self‐reported oral health variables were associated (P < 0.05) with both the HeLD‐29 and the HeLD‐14. Conclusions The reliability, validity and precision of the short‐form version (HeLD‐14) were acceptable when tested in a sample of rural dwelling indigenous Australians. However, it will be important to replicate these findings in other populations before it can be used in health services research to determine the effects of interventions or programs aimed at improving oral health outcomes. This short form will be easy and efficient for use in research and clinical settings.